From promise to practice: evaluating the clinical impact of FcRn inhibition in IgG-mediated autoimmune rheumatic diseases - Yang, Chu Wei; Xia, Ting; Tan, Qing; Jie, Li Gang; Lou, Ai Ju; Li, Xiao Xiao; Maitiyaer, Maierhaba; Huang, Wen Hui; Zheng, Yu; Yu, Shui Lian (Frontiers in Immunology, 2025)
The neonatal Fragment Crystallizable receptor (FcRn) plays a central role in maintaining immunoglobulin (Ig) G homeostasis by protecting IgG from lysosomal degradation and regulating its transcytosis. In recent years, pharmacological inhibition of FcRn has emerged as a promising therapeutic strategy for IgG-mediated aumhctoimmune diseases, including systemic lupus erythematosus, rheumatoid arthritis, anti-Neutrophil Cytoplasmic Antibodies (ANCA) -associated vasculitis, and others. By accelerating the catabolism of circulating IgG, FcRn inhibitors effectively reduced pathogenic autoantibody levels without broadly suppressing other immune components. Several FcRn-targeting agents, such as efgartigimod, rozanolixizumab, and nipocalimab, have demonstrated favorable safety and efficacy profiles in clinical trials and are now approved or under investigation for multiple indications. This review also explored personalized therapeutic approaches, combination strategies, and the future landscape of FcRn-targeted drug development. While FcRn inhibition offered a paradigm shift in managing antibody-driven diseases, long-term safety and patient stratification remain key challenges for future research.